Skrining Bakteriosin dari beberapa Galur Bakteri Asam Laktat Isolat Lokal Genus Streptococcus dan Weissella - RAFIKA SARI; CESILIA ANITA; MAKSUM RADJI; AMARILA MALIK (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Many lactic acid bacteria (LAB) are known to produce antimicrobial peptides, termed bacteriocins. Bacteriocins are ribosomally synthesized antimicrobial peptides which kill closely related bacteria. Bacteria producing bacteriocin are also known to produce bacteriocin immunity protein (bip). This study aimed to identify bacteriocins activity in an attempt to isolate the bacteriocin and the bip. In this study, genus Streptococcus and Weissella from our LAB collection were screened on well diffusion agar for antagonism assay. Growth inhibition zone observation has been carried out by antagonism assay using Leu. mesenteroides TISTR 120, Leu. mesenteroides JCM 6124, Staphylococcus aureus FNCC 0047, Bacillus subtilis FNCC 0061, Escherichia coli FNCC 0183, Salmonella typhi FNCC 0165, Pseudomonas aeruginosa FNCC 0063, and Listeria monocytogenes FNCC 0156 as indicator strains. Protease K, catalase, and trypsin were also used following the first screening assay for confirmation test. Results showed that both Strep. macedonicus MBF10-2 and W. confusa MBF8-1 posses bacteriocin activity although both against Leu. mesenteroides only, the TISTR 120 and JCM 6124 indicator strains